2012
DOI: 10.1002/jobm.201200031
|View full text |Cite
|
Sign up to set email alerts
|

Study of the siderophore‐producing Trichoderma asperellum Q1 on cucumber growth promotion under salt stress

Abstract: Trichoderma spp. are versatile beneficial fungi which can stimulate growth and plant resistance to biotic and abiotic stresses. In this study, the potential of Trichoderma isolate in promoting the cucumber growth under salt stress and its possible mechanisms were investigated. Strain Q1 was isolated from the rhizosphere of cucumber in greenhouse in China and identified as Trichoderma asperellum based on its morphological features and the molecular phylogenetic analyses. It exhibited some plant growth‐promoting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(66 citation statements)
references
References 38 publications
1
63
0
2
Order By: Relevance
“…The species most commonly used in biocontrol include T. harzianum, T. atroviride, T. asperellum, T. polysporum, T. viride, as well as a few species that belong to the related genus of Gliocladium [63]. The antagonistic potential serves as the basis for effective biological control applications of different Trichoderma strains as biofungicides against soil, foliar and vascular pathogens, as an alternative to chemical pesticides for treatment against a wide spectrum of plant pathogens, as well as to increase resistance to abiotic stresses [18,64,65].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The species most commonly used in biocontrol include T. harzianum, T. atroviride, T. asperellum, T. polysporum, T. viride, as well as a few species that belong to the related genus of Gliocladium [63]. The antagonistic potential serves as the basis for effective biological control applications of different Trichoderma strains as biofungicides against soil, foliar and vascular pathogens, as an alternative to chemical pesticides for treatment against a wide spectrum of plant pathogens, as well as to increase resistance to abiotic stresses [18,64,65].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous hypothesis have been proposed to explain this observation including the improvement of chemical solubilisation, sequester, availability (i.e. siderophores production) [65,78,79] and nutrient uptake by the plant [80], as well as the involvement of growth phytohormones from both plant and fungal origin [28,81]. Not only do these processes improve plant growth, but they also stimulate plant respiration, thus enhancing photosynthesis or photosynthetic efficiency [64], as well as increasing the ability of the plant to withstand abiotic stresses such as drought, salinity, high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Siderophore production by Trichoderma spp. was also reported by several workers that enhance the availability of iron to plants (Qi and Zhao 2013).…”
Section: Plant Growth Promoting Characteristicsmentioning
confidence: 85%
“…The research by several independent research groups have observed the increased growth of various crops with the use of antagonist Trichoderma spp. (Sharma et al, 2012;Contreras-Cornejo et al, 2013;Hermosa et al,2013;Samolski et al, 2013;Qi and Zhao, 2013;Stewart and Hill, 2014). In a study conducted by Zhang et al, (2014a) revealed that Trichoderma longibrachiatum was found fairly effective for promoting plant growth and nematode control in wheat.…”
Section: Plant Growth Promotionmentioning
confidence: 99%